Microcapillary Culture Method: A Novel Tool for In Vitro Expansion of Stem Cells from Scarce Sources - Allahverdiyev, Adil M.; Baydar, Serap Yesilkir; Bagirova, Melahat; Findikli, Necati (ELSEVIER SCIENCE INC, 2012)
Background and Aims. Although increasing numbers of studies report the derivation of stem cells from a variety of different tissues, derivation efficiencies greatly vary among different studies even for the same tissue source. Hence, a consistent and efficient isolation protocol has not yet been established to date. Several factors have so far been documented that influence and limit mesenchymal stem cell (MSC) isolation and cultivation, including the age and gender of the tissue donor, origin of the tissue, amount of sampled tissue material and cell culture characteristics including the choice of basal media, serum, gas composition, etc. The aim of the study was to investigate the microcapillary culture method (MCM) to establish an efficient and consistent isolation as well as cultivation protocol by comparing the results with other classic culture systems (flasks, center wells). Methods. MSCs isolated from adipose tissue of different donors were observed comparatively under different culture systems (flasks, center wells, microcapillary tubes) and their proliferation and differentiation were investigated. Flow cytometry was used for immunophenotypic characterization of derived cells and histochemical staining (Oil Red 0 and Alizarin Red S) was applied for determining their differentiation capacity. Results. It has been shown for the first time that AD-MSCs can consistently and efficiently be derived from a scarce amount of adipose tissue by MCM. Conclusions. Further and similar studies should be performed to determine whether this methodology can also be applicable for other MSC sources. (C) 2012 IMSS. Published by Elsevier Inc.
Keywords: Adipose tissue stem cell; Cell culture; Microcapillary culture method; Flow cytometry; VISCERAL LEISHMANIASIS; STROMAL CELLS; DIFFERENTIATION; DIAGNOSIS; Research & Experimental Medicine